2021
DOI: 10.1080/20008198.2021.1930897
|View full text |Cite
|
Sign up to set email alerts
|

HPA-axis activity and the moderating effect of self-esteem in the context of intimate partner violence in Cameroon

Abstract: Background:The experience of intimate partner violence (IPV) is stressful. One objective way to monitor it is to assess victims' stress response by measuring the concentration of their salivary cortisol, the major stress hormone released by the hypothalamic-pituitary-adrenal axis. Objective: We investigated how the IPV experienced by women in Cameroon affects their stress levels and those of their children. Method: We recruited 50 mother-child dyads exposed to IPV and a control group of 25 mother-child dyads. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…In recent works from our group with a larger sample of dyads mother-child exposed to IPV, including the dyads examined in the present paper, we showed on one hand that mothers exposed to IPV compared to the control group have high levels of anxiety and depression symptoms and that their children exhibited high levels of externalizing symptoms such as delinquent and aggressive behaviour (7) and on the other hand exposed mother presented increased HPA-axis activity i.e. higher post-awakening cortisol concentrations (17). Exploring NR3C1 promoter methylation in the region of exon 1F and possible association with total cortisol concentration and symptoms of psychopathology in this sub-sample, can provide a stronger argument for long-term consequences of IPV particularly in an unstudied region like Sub-Saharan Africa where levels of violence are very high.…”
Section: Introductionmentioning
confidence: 62%
“…In recent works from our group with a larger sample of dyads mother-child exposed to IPV, including the dyads examined in the present paper, we showed on one hand that mothers exposed to IPV compared to the control group have high levels of anxiety and depression symptoms and that their children exhibited high levels of externalizing symptoms such as delinquent and aggressive behaviour (7) and on the other hand exposed mother presented increased HPA-axis activity i.e. higher post-awakening cortisol concentrations (17). Exploring NR3C1 promoter methylation in the region of exon 1F and possible association with total cortisol concentration and symptoms of psychopathology in this sub-sample, can provide a stronger argument for long-term consequences of IPV particularly in an unstudied region like Sub-Saharan Africa where levels of violence are very high.…”
Section: Introductionmentioning
confidence: 62%
“…Though the neuroimaging and biomarker studies were not as descriptive, they were comprehensive and included evaluations of Hypothalamic-Pituitary-Adrenal (HPA) dysregulation detected by salivary cortisol levels ( 27 ), magnetic resonance imaging (MRI) including diffusion tensor imaging (DTI) to evaluate brain connectivity and white matter changes ( 20 , 24 ). The authors assessed several anatomic features of the brain including the corpus callosum, the caudal anterior cingulate, the middle temporal gyrus, the left amygdala, and ventral diencephalon, including the thalamus.…”
Section: Resultsmentioning
confidence: 99%
“…Across almost all the studies, the authors make a connection between IPV-induced TBI and health-related support services for victims. The teams of Gass ( 19 ), Joyner ( 21 ), Issahaku ( 22 ), Sedziafa ( 23 ), Saadi ( 26 ), and Wadji ( 27 ) all discuss the need to either increase identification through health-related encounters or improve health-related services to better support victims. In investigating the association between IPV and health seeking behaviors, Gass et al ( 19 ) found that compared with non-abused women, women reporting IPV were 1.5 times more likely to have visited a physician/healthcare facility and nearly twice as likely to have visited a traditional healer in the past 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations